Network intrusion detection and alert system - To, Jin Yi (2024)
Network security has become a critical concern for organizations worldwide as traditional security measures struggle to keep pace with the rapidly evolving landscape of cyber threats. This project aims to develop an intelligent and comprehensive network intrusion detection and alert system (NIDAS) to enhance network security and provide real-time threat mitigation. NIDAS is security technology that enabling security administrators to identify any abnormal or malicious network traffic in real-time. NIDAS will consist of several key components, including deep network traffic packet inspection, behavior analysis, a prevention rules intrusion detection engine, and an alert prioritization and visualization module. The system will be trained on labeled datasets to identify various types of network attacks and anomalies. By employing a multilayered approach, NIDAS will be capable of detecting both known and unknown threats, ensuring comprehensive protection against various attack vectors. The intrusion detection component will utilize a combination of signature-based and anomaly-based detection techniques. Signature-based detection compares network traffic packets with a real-time updated database of known attack patterns, while anomaly-based detection algorithms learn normal behavior patterns and identify deviations. This dual approach will enable the system to effectively detect and respond to both known and zero-day threats. Upon detecting a potential intrusion, the alert system will generate real-time notifications with relevant details such as the nature of the threat, affected network segments, and recommended mitigation strategies. By integrate Zabbix with IDS capabilities system, the system can reduce false positives and improve the accuracy of threat detection. This research project aims to create a comprehensive and robust network security solution that provides greater visibility, transparency, and protection against potential threats. By delivering real-time threat detection and actionable insights, the system will significantly enhance an organization's ability to protect its critical assets and maintain secure network infrastructure in the face of ever-changing network threats.